Implications of Seed Vault Storage Strategies for Conservation of Seed Bacterial Microbiomes - Chandel, Ankush; Mann, Ross; Kaur, Jatinder; Norton, Sally; Edwards, Jacqueline; Spangenberg, German; Sawbridge, Timothy (Frontiers in Microbiology, 2021)
Global seed vaults are important as they conserve plant genetic resources for future breeding to improve crop yield and quality, and to overcome biotic and abiotic stresses. However, little is known about the impact of standard storage procedures, such as seed drying and cold storage on the seed bacterial community, and the ability to recover seed associated bacteria after storage. In this study, soybean (G. max (L.) Merr.) seed were analyzed to characterize changes in the bacterial community composition and culturability under varying storage conditions. The G. max bacterial microbiome was analyzed from undried seed, dried seed and seed stored for 0-, 3-, 6- and 14-months. Storage temperatures consisted of -20°C, 4°C and RT, with -20°C being commonly used in seed storage vaults globally. The seed microbiome of G. max was dominated by Gammaproteobacteria under all conditions. Undried seed was dominated by Pantoea (33.9%) and Pseudomonas (51.1%), however following drying the abundance of Pseudomonas declined significantly (0.9%), Pantoea increased significantly (73.6%), and four genera previously identified including Pajaroellobacter, Nesterenkonia, env.OPS_17 and Acidibacter were undetectable. Subsequent storage at RT, 4°C or -20°C maintained high abundance Genera at the majority of time points, although RT caused greater fluctuations in abundances. For many of the low abundance Genera, storage at -20°C resulted in their gradual disappearance, whereas storage at 4°C or RT resulted in their more rapid disappearance. The changes in seed bacterial composition were reflected by cultured bacterial taxa obtained from the stored G. max seed. The main taxa were largely culturable and had similar relative abundance, while many, but not all of the low abundance taxa were also culturable. Overall, these results indicate that the initial seed drying affects the seed bacterial composition, suggesting microbial isolation prior to seed drying is recommended to conserve these microbes. The standard seed storage condition of -20°C is most suitable for conservation of the bacterial seed microbiome as this storage temperature slows down the loss of seed bacterial diversity over longer time periods, particularly low abundance taxa.